Instances of simplified style in ten English translations of Dane Zajc - Nada Grošelj (Acta Neophilologica, 2003)
The article compares five poems by the Slovenian poet Dane Zajc and two translations of these poems into English. Focusing on the structures which are stylistically marked in Slovenian but neutralised in translation, the article categorises the translation solutions into groups according to how closely they correspond to the original and each other in syntactic form and in organisation of information (the functional sentence perspective), exarnining the instances from each group in detail and deterrnining their relative frequency. It concludes by isolating the three types of marked Slovenian structures which tend to be neutralised in translation: marked word order, structural am biguity, and non-basic constructions, including rhetorical devices.